Understanding charge storage in Nb2CTx MXene as an anode material for lithium ion batteries. Issue 40 (7th October 2021) - Cheng, Renfei; Hu, Tao; Wang, Zuohua; Yang, Jinxing; Dai, Ruqiao; Wang, Weizhen; Cui, Cong; Liang, Yan; Zhang, Chao; Li, Cuiyu; Wang, Hailong; Lu, Hongxia; et al.
Abstract : Multilayered Nb2 CT x MXene with dominant –O functional groups stores charge at the expense of changes in the oxidation states of both transition metals Nb and O, showing a near zero-strain feature upon (de)lithiation. Abstract : MXenes represent an emerging family of two-dimensional materials of transition metal carbides/carbonitrides terminated with functional groups like –O, –OH, and –F on the chemically active surface of MX slabs. As a member of the family, Nb2 CT x exhibits superior lithium storage capacity over most of the other MXenes as anode materials in lithium-ion batteries (LIBs). However, an in-depth understanding of the charge storage mechanism is still lacking so far. Here, through combining complementary experiments and density functional theory calculations, we provide insights into the (de)lithiation process. Specifically, Nb2 CT x with dominant –O functional groups stores charge as a result of changes in the oxidation states of both transition metals Nb and O, which is supported by Bader charge analysis showing a significant change in the oxidation states of Nb and O upon lithiation. As monitored by ex situ X-ray diffraction, the interlayer spacing of Nb2 CT x changes slightly upon lithium ion (de)intercalation, corresponding to a volume change of only 2.3% with a near zero-strain feature. By coupling with a LiFePO4 /C cathode, the full cell presents superior rate capability and cycling stability as well. The insights into the charge storage mechanism of Nb2 CT x in this work provide useful guidance for the rational design of MXene-based anode materials for high-performance LIBs.